A new closed-loop control of the injected mass for a full exploitation of digital and continuous injection-rate shaping. (1st December 2018) - Ferrari, A.; Novara, C.; Paolucci, E.; Vento, O.; Violante, M.; Zhang, T.
Highlights: The benefits of digital and continuous injection rate shaping schedules are shown. A new closed-loop control strategy of the injected mass has been developed for multiple injections. The new control has been implemented in a prototypal hardware and hydraulic tests have been carried out. Abstract: The results of digital and continuous rate shaping strategies are discussed for a low temperature combustion diesel engine. The outcomes show a high potential of these injection schedules for the management of the trade-off between engine out emissions, fuel consumption and combustion noise. However, a weak point has emerged concerning the high value of the coefficient of variation of the indicated mean effective pressure. This is due to instability of the mass that is injected in a multiple injection when the injection shots are closely coupled. An innovative closed-loop control strategy of the injected mass is developed for multiple injections. Pressure time histories, measured along the rail-to-injector pipe, are used to infer the instantaneous mass flow-rate entering the injector. This flow-rate is integrated between two optimized time instants and the thus calculated fuel mass results to correlate well with the injected mass. The new control strategy has been implemented in rapid prototyping hardware and tests have been performed at the hydraulic rig. The prototypal fuel injection system controls the injected mass with an accuracy of 2 mg over the entire dwell time range. A significant improvement has been observed, compared to state-of-the-art injection systems, in the stability of the injected mass for the closely coupled injections.